Guba Lebi︠a︡zhʹi︠a︡ po opisi Gidrograficheskoĭ Ėkspedit︠s︡īi Vostochnago okeana 1916 g. / Kopirovali Kap. d. pl. Ivanovskiĭ i Kap. m. pl. Vshikarevʺ - Russia. Glavnoe gidrograficheskoe upravlenīe (Vladivostok : Morskoe ministerstvo, Glavnoe gidrograficheskoe upravlenīe; Владивосток : Морское министерство, Главное гидрографическое управленіе, 1916)
Main title translation: Lebyazhya Bay, according to the survey of the Hydrographic Expedition of the Eastern Ocean in 1916.; Relief shown by form lines and spot heights. Depth shown by soundings and isolines.; Greenwich meridian.; "Masshtabʺ 1/21000 ili 250 sazh. vʺ di︠u︡ĭmi︠e︡" = Scale 1/21000 or 250 fathoms in 1 inch.; "348" -- bottom right margin Grayscale; 1:21,000